2013
DOI: 10.1111/eci.12170
|View full text |Cite
|
Sign up to set email alerts
|

Familial mediterranean fever: a fascinating model of inherited autoinflammatory disorder

Abstract: Background Familial Mediterranean fever (FMF) is a rare inherited autosomal recessive autoinflammatory disorder characterized by recurrent and self-limited episodes of fever and painful serositis, lasting 1-3 days. FMF occurs almost exclusively among ethnic groups of the Mediterranean basin, although cases have also been found in Japan and Korean populations. Diagnosis is based on clinical features, response to colchicine and genetic analysis. Novel drugs are emerging, allowing better management of colchicine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 114 publications
0
26
1
2
Order By: Relevance
“…It is characterized by recurrent and self-limited episodes of fever and painful serositis, related to neutrophil activation at serosal surfaces. It affects predominantly ethnic groups around the Mediterranean basin [74]. Colchicine represents the standard first line treatment for FMF and has to be continued for life.…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by recurrent and self-limited episodes of fever and painful serositis, related to neutrophil activation at serosal surfaces. It affects predominantly ethnic groups around the Mediterranean basin [74]. Colchicine represents the standard first line treatment for FMF and has to be continued for life.…”
Section: Resultsmentioning
confidence: 99%
“…44 Familial Mediterranean fever is caused by mutations in the gene for pyrin, a myeloid-lineage protein that regulates inflammasome activation. 45–48 Pyrin gene mutations lower the threshold for IL-1β production and inflammatory attacks.…”
Section: Colchicine In Rheumatic Diseasesmentioning
confidence: 99%
“…32 None of our FMF patients were resistant to colchicine treatment although previous studies suggested that 10% to 15% of FMF patients have resistance to colchicine treatment. 33,34 Well-controlled disease with colchicine treatment might have resulted in suppression of the auto-inflammation, thus the need of carnitine. Also, insidious skeletal muscle damage might have resulted in elevated FC levels in FMF patients.…”
Section: Discussionmentioning
confidence: 99%